Evaluation of Management of Seed Supply in Oilseeds and Pulses in Rajasthan - Planning Commission (Planning Commission, 2001)
India witnessed an impressive growth in agricultural production, mainly in foodgrains, after the introduction of green revolution technology in mid 60’s, which was based on use of proper combination of quality seeds, irrigation and fertilisers. As a result thereof, foodgrains production of India rose from 72.35 million tonnes in 1965-66 to 199.44 million tonnes in 1996-97 and foodgrains yield rose from 6.29 qtrs./ha. to 16.14 qtrs./ha.
Rajasthan
Rajasthan